Automated Assessment of Pavlovian Conditioned Freezing and Shock Reactivity in Mice Using the Video Freeze System - Anagnostaras, Stephan G.; Wood, Suzanne C.; Shuman, Tristan; Cai, Denise J.; LeDuc, Arthur D.; Zurn, Karl R.; Zurn, J. Brooks; Sage, Jennifer R.; Herrera, Gerald M. (Frontiers in Behavioral Neuroscience, 2010)
The Pavlovian conditioned freezing paradigm has become a prominent mouse and rat model of learning and memory, as well as of pathological fear. Due to its efficiency, reproducibility, and well-defined neurobiology, the paradigm has become widely adopted in large-scale genetic and pharmacological screens. However, one major shortcoming of the use of freezing behavior has been that it has required the use of tedious hand scoring, or a variety of proprietary automated methods that are often poorly validated or difficult to obtain and implement. Here we report an extensive validation of the Video Freeze system in mice, a “turn-key” all-inclusive system for fear conditioning in small animals. Using digital video and near-infrared lighting, the system achieved outstanding performance in scoring both freezing and movement. Given the large-scale adoption of the conditioned freezing paradigm, we encourage similar validation of other automated systems for scoring freezing, or other behaviors.